The relationship among image, satisfaction and loyalty – innovative factor of competitiveness for shopping centers - Ioana-Nicoleta Abrudan; Ioan Plăiaș; Dan Cristian Dabija (Amfiteatru Economic Journal, 2015)
Currently, most markets are characterized by high competition among shopping centers. Under these circumstances, the evolution in the competitiveness and performance of the centers is increasingly linked to the success in the innovation of current activities, which is aimed at improving their image and increasing customer satisfaction and loyalty. The purpose of the present research is to study the influence of innovation activities through the image components on behavioural loyalty, mediated by satisfaction (affective loyalty) and conative loyalty. The authors aim to investigate, using a questionnaire survey among the customers of Cluj-Napoca shopping centers, the relationship among the components of image and satisfaction and the various types of loyalty. The conclusions of the structural equations modelling reveal that most components of the image (assortment, price, loyalty policy, décor, service and communication) directly and positively influence satisfaction, and that satisfaction and conative loyalty mediate the relationship between image and behavioural loyalty. The results reveal important managerial implications from the point of view of innovative actions of shopping centers, which can contribute to attracting and keeping customers, these contributing not only to creating loyal patrons, but also to increasing their competitiveness and to achieving better positioning.
Keywords: M31; M10; 330; consumer satisfaction; cognitive; affective; conative and behavioural loyalty; image; retail; shopping centers; innovation; competitiveness